Early Alveolar Bone Grafting Is Associated with Lower Regraft Rates and Improvements in Long-Term Psychosocial Outcomes. Issue 1 (21st December 2021) - Hu, Allison C.; Jain, Nirbhay S.; Chan, Candace H.; Malapati, Sri Harshini; Dang, Brian N.; Bertrand, Anthony A.; Squitieri, Lee; Wilson, Libby F.; Lee, Justine C.
Abstract : Background: Late childhood (8 to 10 years of age) has emerged as a vulnerable period in children with cleft and craniofacial anomalies such that increased interventions during this period are associated with worse long-term patient-reported anxiety and depressive symptoms. These findings suggest that one possible practice change may be to consider changes in timing for surgical treatment algorithms. In this work, the authors investigated outcomes in altering the timing of the most common operation in late childhood for cleft lip and palate patients, alveolar bone grafting. Methods: A two-part, multi-institutional cohort study was conducted. To understand the feasibility of changing alveolar bone graft timing with respect to surgical success, reoperation rates were retrospectively compared among patients grafted at different ages (4 to 7, 8 to 10, and 11 to 13 years of age). To understand the long-term effect of changing alveolar bone graft timing on psychosocial outcomes, the psychosocial suite of the Patient-Reported Outcomes Measurement Information System was prospectively administered to teenagers and adults with cleft lip and palate. Results: Among the three age groups, early grafting (4 to 7 years of age) demonstrated the lowest regraft rates compared with the other groups. As these results suggested that early grafting is a viable alternative to standard timing, we next compared the differences in long-term psychosocial outcomes. Patients who were grafted early reported lower levels of anxiety and depressive symptoms as teenagers and adults. Conclusion: Altering timing of one stage in cleft lip and palate reconstruction to an earlier age decreases regraft rates and improves long-term patient-reported anxiety and depressive symptoms. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.